High‐Efficiency Wideband Excitable Mechanoluminescence from a Yellow MOF Phosphor as White LED and Multicolor Thin Films. Issue 3 (23rd November 2021) - Ma, Xiao; Xu, Xiaojing; Duan, Fengnan; Huang, Wei; Chen, Qun; Wu, Dayu
Abstract: High‐efficiency multifunctional metal‐organic framework (MOF) phosphor is highly desired for various practical applications, such as in lighting, anticounterfeiting, sensing, and so on. Herein, a highly yellow‐emitting MOF (Zn‐TPPA) phosphor is prepared via mechanical grinding for application as white light‐emitting diode (LED) and composite films. Under UV or visible‐light excitation, Zn‐TPPA exhibits the intense cyan emission (λem  = 497 nm) with a high photoluminescence quantum yield (PLQY). Zn‐TPPA undergoes an intriguing reversible mechanochromic luminescence through mechanical stimuli (grinding). Notably, the grinding not only induces emissive color changes from cyan to yellow but also obviously enhances the luminescence.More significantly, upon excitation with blue light (λex  = 460 nm), the PLQY of yellow light approaches as high as 92.7 (±1.8) %, which makes the yellow MOF phosphor potential as high‐performance white LED. In addition, the MOF‐based composite films exhibit dual emission and excitation‐dependent emission color due to the presence of two emission sources (TPPA monomer and aggregation state). Hence, Zn‐TPPA with reversible mechanochromic luminescence would have potentials in the fields of luminescence sensor, display, and anticounterfeiting. Abstract : A high‐efficiency yellow metal‐organic framework (MOF) phosphor displays an intriguing reversible mechanoluminescence. Grinding not only induces emissive color changes but also induces the photoluminescence quantum yield (PLQY) enhancement. Significantly, upon excitation with blue light, luminescent MOF emits yellow light with a high PLQY, which is applicable as high‐performance white light‐emitting diode and multi‐color composite films.